Influence of FDI on tourism in Crostia - Zoran Ivanovic; Suzana Baresa; Sinisa Bogdan (UTMS Journal of Economics, 2011)
Tourism is one of the most rapidly growing industries in the world. Many developing countries consider it as possibility for raising export earnings. Most important role in the internationalization of production has foreign direct investment. This paper investigates the contribution of FDI (Foreign direct investment) on economic growth, how does it reflect on tourism in Croatia. FDI are important for development of technology, unfortunately most foreign investment went to infrastructure, in terms of high unemployment and stagnating exports priority should be investment in the industrial structure since they have the greatest multiplier effect overall economic growth. Croatian export structure is obsolete. The share of technologically advanced products is small.
Keywords: 330; FDI; GDP; tourism in Croatia; foreign investors